2018
DOI: 10.2478/alife-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

Study of Rural Groundwater Quality in Brestea Village, Romania

Abstract: Water is a social requirement and an important factor in the ecological balance. Water from wells is good for direct consumption if the soil is not contaminated. The quality of drinking water is regulated by Law no. 458/2002 (transposing the Directive 98/83/EC on the quality of drinking water). The aim of this paper was to assess the physicochemical qualities of groundwaters from Brestea village, commune Denta, Timis County. The water samples were taken in 2015 from 10 functional wells. For the source whose ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The peroxide value results showed no significant (p>0.05) difference among the three oil samples. The PV has correlation to the oxidation and the stability of the oils whereas the low values indicate to high stability [16]. In this study, the PV was observed to be low for SBO and VCO that indicated their high stability.…”
Section: Resultsmentioning
confidence: 52%
“…The peroxide value results showed no significant (p>0.05) difference among the three oil samples. The PV has correlation to the oxidation and the stability of the oils whereas the low values indicate to high stability [16]. In this study, the PV was observed to be low for SBO and VCO that indicated their high stability.…”
Section: Resultsmentioning
confidence: 52%
“…The quality and composition of the plant material depend on the climatic conditions, the physico-chemical and biological properties of water and soil (influenced by excessive pollution with chemicals, pharmaceuticals, household waste, zootechnics, etc.) in the plant vegetation area [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Extraction Of the Volatile Oilsmentioning
confidence: 99%
“…Obviously, along with other soil components, enzymes are also influenced by the environmental conditions, so that all the qualities and properties of the soil and the environment quality are reflected in the production of vegetables or fruits and by their nutritional content [4][5][6][7][8][9]. At the same time, a strong impact on the composition and quality of agricultural soil is caused by inappropriate discharges of domestic waste, animal husbandry, industrial waste (especially chemical, medical and pharmaceutical, petroleum) [10][11][12][13][14][15][16][17][18][19][20], and waste water etc. [21][22][23][24][25].…”
mentioning
confidence: 99%
“…At the same time, a strong impact on the composition and quality of agricultural soil is caused by inappropriate discharges of domestic waste, animal husbandry, industrial waste (especially chemical, medical and pharmaceutical, petroleum) [10][11][12][13][14][15][16][17][18][19][20], and waste water etc. [21][22][23][24][25].…”
mentioning
confidence: 99%